Central Shrine of the Garbhagriha of the Adinatha Temple - Temples of India Project Team (Jio Institute, 2024)
The main central shrine of the garbhagriha (sanctum sanctorum) has a high pedestal having a cupola (a rounded dome with a ceiling) like design. This pedestal has three sculptures, of which the central one is shown sitting on a lotus pedestal. Unlike the side shrine, the roof here is highly ornamented with meenakari (enamel) art that includes plenty of golden embossing.